Toxicity of L-asparaginase drugs in acute lymphoblastic leukemia treatment - T. T. Valiev (Онкогематология)
Currently no therapy of acute lymphoblastic leukemia is conceivable without L-asparaginase drugs, with its antileukemic effect by extracellular asparagine depletion, thus preventing its admission to leukemic cell. Besides high antitumor effect, L-asparaginase drugs have side and toxic effects, such as hypersensitivity reactions, thrombosis, pancreatitis / pancreatic necrosis, and hepatotoxicity. For L-asparaginase safety profile improvement a technology of pegylation was lay down and PEG-aspargase drug produced. This drug has less toxic effects and recommended as first-line therapy of acute lymphoblastic leukemia. Drug monitoring for assessment the effectiveness and toxicity of L-asparaginase is optimal. Such therapy individualization helps for L-asparaginase dose finding and decrease frequency and severity of side effects.